Dengue shock syndrome in an infant - Aurpibul L. (BMJ Publishing Group, 2014)
Dengue is a mosquito-borne infection affecting children and adults worldwide. In newborn infants, the dengue virus can cause diseases, especially in infants born to pregnant women hospitalised with dengue or postpartum women with fever. The authors report a case of a term newborn infant who presented with haemodynamic instability and thrombocytopaenia at the age of 7 days, without a history of clinical dengue infection in the mother. The physical examination revealed an afebrile and drowsy infant with a petechial rash all over the body and ecchymosis on both palms and soles. The authors confirmed the diagnosis using the dengue NS1 antigen on the first day of admission. The treatment included fluid management and platelet transfusion. The patient recovered well and was discharged from the hospital on the 10th day of hospitalisation. Copyright 2014 BMJ Publishing Group. All rights reserved.